Padronização do método experimental para avaliação do efeito da combinação de extratos naturais e fotobiomodulação na viabilidade de queratinócitos submetidos ao estresse induzido por radiação ultravioleta A - Silva, Elineides Santos (2016)
Skin presents different functions, such as coating, temperature control, eliminating chemicals, etc.The skin exposure to UV radiation may cause some alterations related to premature aging and skin cancer. Studies have shown that plant extracts with antioxidant properties reduce the effects of photoaging; in parallel, the bioestimulating effect of visible light may promote bioenergetic, bioelectrical and biochemical changes. In this sense, the combination of natural antioxidants and phototherapy is an interesting strategy to promote skin rejuvenation. The objective of the project is to standardize the parameters of the experimental protocol to evaluate the effect of the combination of natural extracts and photobiomodulation on the viability of immortalized normal human keratinocytes subjected to photoinduced damage by Ultraviolet type A (UVA). Some extracts, previously selected by their phytochemical family, were evaluated: Chamomile and Rosemary (Flavones), Blueberry (Anthocyanines), Green tea (Catechins), Fig (Coumarines), Pomegranate (Ellagic Tannin) and Walnut (Gallic Tannin). Human immortal keratinocytes in culture (HaCaT) were used as experimental model. Simulating UVA exposure, a system was used (366 ± 10 nm; 2.5 mW / cm2). A Light Emitting Diode (LED) cluster were used for phototherapy (640 ± 12.5 nm; 2.6 mW / cm2). The percentage of living cells was determined by MTT method. The viability assessment was performed using the MTT method, comparing the toxicity in relation to the control group. The experimental parameters defined were 60 minutes of irradiation with UVA (9 J/cm2), 7 minutes of LED irradiation (1 J/cm2) and, depending on the polyphenolic content of each extract, concentrations of 0.01 to 0.3 % v/v of extracts.